Pooled Analysis of the Routine Nasogastric Decompression Necessity for Elective Gastrectomy - Ping Yang (Shiraz University of Medical Sciences, 2019)
Background: Nasogastric decompression is routinely used for intestinal drainage or decompression after gastrectomy. However,nowadays its efficacy is under debate.Objectives: The purpose of this study was to investigate the efficacy and necessity of nasogastric decompression in radical gastrectomyfor gastric cancer.Methods: Two PubMed and EMBASE electronic databases were retrieved by November 2018. A prospective randomized controlledtrial (RCT) and comparison of nasogastric decompression with and without nasogastric decompression after gastrectomy are requiredfor eligible studies.Results: A total of 1,885 cases were included in 13 randomized controlled studies. There were 941 cases in nasogastric decompressiongroup and 944 cases in non-nasogastric decompression group after gastrectomy. The patients in non-nasogastric decompressiongroup had significantly shorter time of bowel sound return (WMD = -0.20, 95% CIs = -0.38 - 0.02, P = 0.03), shorter time of first oralintake (WMD = -0.58, 95% CIs = -0.92 - 0.24, P = 0.0007), faster tolerance to semi-solid diet (WMD = -0.65, 95% CIs = -0.96 - 0.34, P <0.0001), and shorter time of postoperative hospital stay (WMD = -0.99, 95% CIs = -1.70 - 0.27, P = 0.007). No statistically significantdifferences were observed in the first time to passage of flatus, vomiting, mortality rates, total complications, gastrointestinal complications,wound complications, respiratory complications, anastomosis or duodenal stump fistula, and general complications.Conclusions: The routine nasogastric decompression was not recommended for patients after elective gastrectomy.